(untitled) (Sains Humanika, 2017)
This article focuses on the discussion about the positions of the human mind and prophetic revelations in Islamic research. In the usual Social Science research, only the human mind serves as the basis for proofs and theory of knowledge (epistemology). The research would reject prophetic revelations. In Islam, however, there is a consensus that prophetic revelations must be placed as better proofs and theory of knowledge over the the human mind. As such, what are the positions of prophetic revelations and the human mind in Islamic research? To answer this question, logic is used as reference. Logic is the study of arguments based on human reasoning, as defined in Islam. Logic also serves as a method of determining the validity of proofs which can be used in an argument. The questions which arise then, are: What is the position of the human mind in Islamic research? What is the order of priority between the human mind and prophetic revelations in an Islamic research? To answer these questions, this paperwork will use literary research and textual analysis to analyse the positions of prophetic revelations and the human mind according to logic. This article will study the definitions of the human mind and prophetic revelation in Islam. Then the positions of the human mind and prophetic revelations will be analysed in a logical discussion, to serve as a method to be used in Islamic research. The use of logic is observed as having cleared the confusion in determining the positions of the human mind and prophetic revelations in Islamic research. How the prophetic revelations are used in Islamic research in accordance to the Islamic research method is also discussed. The results of this research found that logic approves of both the â€œnaqliâ€ and â€œaqliâ€ proofs. The human mind is actually recognised as a legitimate instrument for proofs in Islam but it cannot take precedence over prophetic revelations. Instead, prophetic revelations serve an important role in Islamic research. However, certain methods must be followed when using the prophetic revelations in Islamic research in order for them to be valid.